Sustained censorship in KW (2026-02) (Kuwait) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Kuwait. Data sourced from OONI.
Censorship Incident ID: KW-2026-0130. Severity: critical. Confidence: 80%